FIRST GENERATION VS SECOND GENERATION: IDENTITY CLASH ANALYSIS OF PAKISTANI DIASPORA IN IRAM HAQ’S WHAT WILL PEOPLE SAY? IDENTITY CLASH ANALYSIS OF PAKISTANI DIASPORA IN IRAM HAQ’S WHAT WILL PEOPLE SAY? - Hamzah, Nanda Nabilla (LPPM Universitas Bumigora Mataram, 2019)
This paper is based on a qualitative study of identity clash of the first and the second generation of Pakistani diaspora in What Will People Say movie. The paper aims to discuss the multifarious different behaviors shown in the movie in which represented by the Parents as the first generation diaspora and the Child as the second generation diaspora. The meaning and social belonging are established in this context is then analysed. By using Homi’s representation and identity theory, some of the general social and cultural processes which influence both generation as individuals and as a minority group are then illustrated by the behaviours that subsequently create their identity. The study shows that the different behaviours between the first and the second diaspora generation that occur in the movie is inevitable. The first generation is strongly value the cultural feature of their homeland, meanwhile the second generation slowly but surely forgetting her roots as a Pakistani.